1 × 2 × 3 1 + 2 × 3 × 4 1 + 3 × 4 × 5 1 + . . . + 9 8 × 9 9 × 1 0 0 1 .
The expression above can be expressed in a form of p 1 − q 1 , where p and q are positive integers. Find the value of p + q .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
First, let's determine the pattern.
1 × 2 × 3 1 = 6 1
1 × 2 × 3 1 + 2 × 3 × 4 1 = 2 4 5
Then, we have the pattern
1 × 2 × 3 1 + 2 × 3 × 4 1 + . . . + ( n − 2 ) ( n − 1 ) ( n ) 1
= ( 2 1 − ( n ) ( n − 1 ) 1 ) ( 2 1 ) .
Now, put n = 1 0 0 , we have
( 2 1 − 9 9 0 0 1 ) ( 2 1 )
= 4 1 − 1 9 8 0 0 1 = p 1 − q 1
p = 4 and q = 1 9 8 0 0
Hence, the answer is p + q = 1 9 8 0 4 .
Problem Loading...
Note Loading...
Set Loading...
S = 1 × 2 × 3 1 + 2 × 3 × 4 1 + 3 × 4 × 5 1 + . . . + 9 8 × 9 9 × 1 0 0 1 = n = 1 ∑ 9 8 n ( n + 1 ) ( n + 2 ) 1 Using partial fractions = 2 1 n = 1 ∑ 9 8 ( n 1 − n + 1 2 + n + 2 1 ) = 2 1 n = 1 ∑ 9 8 ( n 1 − n + 1 1 − n + 1 1 + n + 2 1 ) By telescoping = 2 1 ( 1 1 − 9 9 1 − 2 1 + 1 0 0 1 ) = 1 9 8 0 0 4 9 4 9 = 1 9 8 0 0 4 9 5 0 − 1 Multiply up and down by 4 = 4 ( 1 9 8 0 0 ) 1 9 8 0 0 − 4 Note that p 1 − q 1 = p q q − p = 4 1 − 1 9 8 0 0 1
⟹ p + q = 4 + 1 9 8 0 0 = 1 9 8 0 4